Parents decision factors for cohlear implantation and their satisfaction with rehabilitation outcomes - Radić-Šestić Marina; Šešum Mia; Isaković Ljubica (Specijalna Edukacija i Rehabilitacija, 2018)
A cochlear implant is a device that provides hearing sensations for severely and profoundly deaf individuals who derive no significant benefit from hearing aids. Parents are essential for the care and support of a cochlear implanted child. Parental involvement in the rehabilitation process affects the child's better development results. In this study, we examined the factors that influence the decision-making process of parents for implantation of their child, as well as outcomes after implantation. The research was conducted on a sample of 40 respondents, consisting of 20 fathers and 20 mothers. It was implemented in 'Dečija kuća', KBC Zvezdara, in Belgrade. The scale called 'Children with cochlear implant: parents' perspectives' (Archbold et al., 2002), was used for the purpose of this research. The results of this research indicate that parents of children with profound hearing impairment, compared to the parents of children with severe hearing impairment, showed significantly higher assurance in their own decision on implantation. Also, the satisfaction with the results of rehabilitation in some examined segments was influenced by the sex and level of education of the respondents.